Hush : an Irish princess' tale - Napoli, Donna Jo, 1948- (New York : Atheneum Books for Young Readers, 2007)
Fifteen-year-old Melkorka, an Irish princess, is kidnapped by Russian slave traders and not only learns how to survive but to challenge some of the brutality of her captors, who are fascinated by her apparent muteness and the possibility that she is enchanted.
Kirkus Starred.
Pub Weekly.
School Library Journal starred.
Young Adult
Keywords: Conduct of life -- Juvenile fiction; Middle Ages -- Juvenile fiction; Princesses -- Juvenile fiction; Seafaring life -- Juvenile fiction; Selective mutism -- Juvenile fiction; Slavery -- Juvenile fiction; Conduct of life -- Fiction; Historical fiction; Middle Ages -- Fiction; Princesses -- Fiction; Seafaring life -- Fiction; Selective mutism -- Fiction; Slavery -- Fiction; Conduct of life -- Fiction; Historical fiction; Middle Ages -- Fiction; Princesses -- Fiction; Seafaring life -- Fiction; Slavery -- Fiction; Ireland -- History -- To 1172 -- Juvenile fiction; Ireland -- History -- To 1172 -- Fiction; Ireland -- History -- Fiction